Identifikasi Upaya Guru Dalam Menyediakan Media Pembelajaran Sejarah Di SMA Negeri 5 Langsa - Bella, Sita Bella; Junaidi, Teuku (Program Studi Pendidikan Sejarah - Universitas Samudra, 2024)
ABSTRACT This study aims to find out how the teacher's efforts in providing history learning media and to find out the teacher's obstacles in providing history learning media. The method used is qualitative research with a descriptive research approach. The subjects studied were teachers in the field of history education at SMA Negeri 5 Langsa which consisted of 4 teachers, while the object of this research was the identification of teachers' efforts in providing history learning media. Based on observations and interviews that researchers have conducted, it is obtained that several teachers at SMA Negeri 5 Langsa have attempted to provide learning media such as utilizing the media provided by the school in the form of learning resources such as books using existing tools in the school environment such as atlases or maps. Make your own learning media such as audio-visual media that the history teacher takes from the internet and then edits it according to the material to be taught. Doing an internet search following the training provided by the Ministry of Education and Culture regarding the history learning process that will make teachers more skilled in using the media and operating it. The problem is that some teachers are not optimal in using technology so that they are not optimal in using history learning media.